PSYCHOCORRECTIONAL METHODS OF FORMING RELATIONSHIPS WITH CONFLICT ADOLESCENTS IN THE WORK OF SCHOOL PSYCHOLOGISTS (ResearchJet Journal of Analysis and Inventions, 2022)
This article discusses the specifics of interpersonal relationships during adolescence and the use of psychocorrectional methods in conflict situations between adolescents.